Time-domain optical coherence tomography system for determining the extinction coefficient and refractive index of gelatin-based skin phantoms - Mandia, Paulito Fikingas (Animo Repository, 2021)
Optical Coherence Tomography (OCT) is a non-invasive, non-destructive optical imaging technique that uses a low coherence interferometer to obtain real-time cross-sectional images and three-dimensional images of a biological tissue sample. OCT is notably used in biomedical applications including ophthalmology and dermatology. Aside from generating cross-sectional images of the sample, axial scans can also provide additional information about its optical properties such as extinction coefficient (EC) and refractive index (RI). This study determines the EC and RI of gelatin-based skin phantoms using a portable time-domain (TD) – OCT system. The gelatin-based skin phantoms were fabricated with varying concentrations of titanium dioxide (TiO2). By changing the proportion of the gelatin powder and TiO2, skin phantoms can then be fabricated to mimic various skin conditions, both pathologic and non-pathologic. The performance of the constructed portable TD-OCT system was also evaluated. The OCT system has an SNR ranging from 30.04 dB to 42.73dB. The depth profile produced by the OCT is accurate as indicated by the distance measurement conducted. The OCT system was capable of generating B-scans, but the long acquisition times prevent it from obtaining B-scans for in vivo studies or for samples with volatile components. Results of the study found a negligible correlation of EC with TiO2 concentration. Whereas, the RI had a very strong correlation with TiO2 concentration. The median EC values of the phantoms ranged from 4.29/mm to 8.48/mm. Samples of porcine skin were also studied for EC, and the median values ranged from 2.45-6.33. Literature showed that epidermis can have EC of 1.64-7.3/mm. For RI of the phantoms, values ranged from 1.32 to 1.48, while studies on human participants showed that human skin has RI values of 1.34-1.56. Based on EC and RI, it is feasible to fabricate phantoms mimicking human and porcine skin.